Microeconomic theory : a graphical analysis - Bilas, Richard A. (New York : McGraw-Hill, 1967)
This book seeks to present the pure concepts of microeconomics theory at a level comprehensible to juniors, seniors, and first-year graduate students.
Includes bibliographical references and index.
rpm 19/09/2017
Loans
Keywords: Economics